Oral Care Evaluation to Prevent Oral Mucositis in Estrogen Receptor‐Positive Metastatic Breast Cancer Patients Treated with Everolimus (Oral Care‐BC): A Randomized Controlled Phase III Trial. (8th October 2019) - Niikura, Naoki; Nakatukasa, Katsuhiko; Amemiya, Takeshi; Watanabe, Ken‐ichi; Hata, Hironobu; Kikawa, Yuichiro; Taniike, Naoki; Yamanaka, Takashi; Mitsunaga, Sachiyo; Nakagami, Kazuhiko; Adachi, Moriyasu; Kondo, Naoto; et al.
Abstract: Background: The incidence of oral mucositis (any grade) after everolimus treatment is 58% in the general population and 81% in Asian patients. This study hypothesized that professional oral care (POC) before everolimus treatment could reduce the incidence of everolimus‐induced oral mucositis. Materials and Methods: This randomized, multicenter, open‐label, phase III study evaluated the efficacy of POC in preventing everolimus‐induced mucositis. Patients were randomized into POC and control groups (1:1 ratio) and received everolimus with exemestane. Patients in the POC group underwent teeth surface cleaning, scaling, and tongue cleaning before everolimus initiation and continued to receive weekly POC throughout the 8‐week treatment period. Patients in the control group brushed their own teeth and gargled with 0.9% sodium chloride solution or water. The primary endpoint was the incidence of all grades of oral mucositis. We targeted acquisition of 200 patients with a 2‐sided type I error rate of 5% and 80% power to detect 25% risk reduction. Results: Between March 2015 and December 2017, we enrolled 175 women from 31 institutions, of which five did not receive the protocol treatment and were excluded. Over the 8 weeks, the incidence of grade 1 oral mucositis was significantly different between the POC group (76.5%, 62 of 82 patients) and control group (89.7%, 78 of 87 patients; p = .034). The incidence of grade 2 (severe) oral mucositis was also significantly different between the POC group (34.6%, 28 of 82 patients) and control group (54%, 47 of 87 patients; p = .015). As a result of oral mucositis, 18 (22.0%) patients in the POC group and 28 (32.2%) in the control group had to undergo everolimus dose reduction. Conclusion: POC reduced the incidence and severity of oral mucositis in patients receiving everolimus and exemestane. This might be considered as a treatment option of oral care for patients undergoing this treatment. Clinical trial identification number : NCT 02069093. Implications for Practice: The Oral Care‐BC trial that prophylactically used professional oral care (POC), available worldwide, did not show a greater than 25% difference in mucositis. The 12% difference in grade 1 or higher mucositis and especially the ∼20% difference in grade 2 mucositis are likely clinically meaningful to patients. POC before treatment should be considered as a treatment option of oral care for postmenopausal patients who are receiving everolimus and exemestane for treatment of hormone receptor‐positive, HER2‐negative advanced breast cancer and metastatic breast cancer. However, POC was not adequate for prophylactic oral mucositis in these patients, and dexamethasone mouthwash prophylaxis is standard treatment before everolimus. Abstract : Oral mucositis is a clinically significant complication of mucotoxic cancer therapy. This article focuses on the effect of dental intervention, before everolimus treatment, on oral mucositis.